Karakteristik Hunian Bertinggal di Pinggiran Sungai Desa Kota Lintang Bawah, Aceh Tamiang - Mayang, Mayang; Deni, Deni; Olivia, Sisca (Rifa'Institute, 2023)
Providing housing with limited land reserves. With the increasing population, people use riverside land to build housing. River bank settlements are settlements that still exist today, even though many cases of evictions or natural disasters have occurred in these settlements. House buildings on the banks of rivers have Government Regulation Law article 5 paragraph 1 embankments that have not been completely flooded with a width of approximately 5 meters outward along the foot of the bank. The aim of the research is to find out the characteristics of residences on the banks of rivers to solve the problems that exist in the construction of residences in lower latitude urban villages, therefore requiring an approach to the physical use value of residences that is suitable for those with low incomes. The object of research taken from this research is residences located on the banks of the river in Kota Lintang Bawah Village, seen from residential mobility by knowing the characteristics of people in the world. According to John FC Turner, community characteristics are classified into three categories, namely bridgeheader, consolidator and status seeker. This research uses mixed methods. By getting in-depth information about the physical and non-physical forms of buildings located on the banks of rivers with low-income communities. Based on the research results, it shows that the characteristics of residences living on the banks of the river in the Village of Kota Lintang Bawah Aceh Tamiang are classified as bridgeheaders and consolidators.